Oznaki prawdziwego opętania - Wolicki, Marian (Studia Pastoralne, 2026)
The author discusses in this article a problem, important for the practice of pastoral care, of the manifestations of possession. He first cites the symptoms listed in the „Ritual of exorcism”, as well as in the opinions of well-known theologians. The symptoms are then discussed by division into three groups: physical, mental and spiritual. The first includes: unusual strength of a destructive nature, hearing strange voices, visual and auditory hallucinations, somatic disorders, self-injurious behavior, the phenomenon of telekinesis. Psychiatric symptoms include unusual knowledge; non-learned language skills; the symptoms of blockage of the mind, emotions and will; disintegration of the psyche. For the spiritual side we include an aversion to people and holy things, blasphemy, disruption of conscience, despair and suicidal thoughts, and Satan-worship.